Cellulose-based self-healing hydrogel through boronic ester bonds with excellent biocompatibility and conductivity. Issue 19 (19th March 2020) - An, Heng; Bo, Yunyi; Chen, Danyang; Wang, Yong; Wang, Haijun; He, Yingna; Qin, Jianglei
Abstract : Self-healing hydrogel with excellent biocompatibility and conductivity fabricated from cellulose through boronic ester bond. Abstract : Self-healing hydrogels based on degradable resources have developed rapidly in the past decade due to their extensive bioapplications with biosecurity. In this research, a new kind of cellulose-based self-healing hydrogel with bio-degradability is constructed through boronic ester linkage. The carboxyethyl cellulose- graft -phenylboronic acid (CMC–B(OH)2 ) was synthesized through condensation reaction conveniently and then hydrogels were prepared with dynamic boronic ester cross-linking. The chemical structures, microscopic morphologies, mechanical and self-healing properties of the hydrogels were investigated intensively through Fourier transform infrared (FT-IR) spectroscopy, rheological, SEM and tensile testing. The hydrogels formed instantly without any additional catalyst and exhibit excellent self-healing ability with good mechanical properties. Moreover, the hydrogels were applied for controlled release of doxorubicin (DOX·HCl) and showed a successive slow release profile. Importantly, the hydrogel exhibited excellent biocompatibility and show potential applications in controlled drug delivery, 3D cell culture and tissue engineering.